Pemanfaatan Daun Sagu Untuk Atap Dan Dinding Rumah Kumbung - Masdjudi Masdjudi; M Galih Permadi; Indah Widanarti (Faculty of Agriculture, Musamus University, 2019)
The purpose of this study is to provide a solution about the limitations of capital in the construction of kumbung house to open a business of oyster mushrooms in the region of Merauke in creating a suitable microclimate for the growth of oyster mushrooms. The study was conducted by building a kumbung house and oyster mushroom cultivation activities in it. The variables observed in this study include temperature, humidity and oyster mushroom production. The result of this research is sago leaves can be made solution for the construction of kumbung house with relatively cheap cost with cost Rp. 1.947.000, the microclimate created inside the kumbung house that is the temperature in the range of 23ÂºC - 29.2ÂºC and RH in the range of 88% - 99%.